Severity in Plasmodium vivax malaria claiming global vigilance and exploration – a tertiary care centre-based cohort study - Saravu, Kavitha (Malar J, 2014)
BACKGROUND: Mounting reports on severe Plasmodium vivax malaria from across the globe have raised concerns among the scientific community. However, the risk of P. vivax resulting in complicated malaria and mortality is not as firmly established as it is with Plasmodium falciparum. This study was conducted to determine the severity proportion and factors associated with severity in cases of vivax and falciparum malaria. METHODS: Adult patients microscopically diagnosed to have P. vivax/P. falciparum infections from the year 2007-2011 were evaluated based on their hospital records. Severe malaria was defined as per the World Health Organization’s guidelines. Comparison was made across species and binary logistic regression was used to determine risk factors of severity. RESULTS: Of 922 malaria cases included in the study, P. vivax was the largest (63.4%, 95% confidence interval (CI) 60.3-66.5%) infecting species, followed by P. falciparum (34.4%, 95% CI 31.3-37.5%) and their mixed infection (2.2%, 95% CI 1.3-3.2%). Severity in P. vivax and P. falciparum was noted to be 16.9% (95% CI 13.9-19.9%) and 36.3% (95% CI 31.0-41.6%) respectively. Plasmodium falciparum had significantly higher odds [adjusted odds ratio (95% CI), 2.80 (2.04-3.83)] of severe malaria than P. vivax. Rising respiratory rate [1.29 (1.15-1.46)], falling systolic blood pressure [0.96 (0.93-0.99)], leucocytosis [12.87 (1.43-115.93)] and haematuria [59.36 (13.51-260.81)] were the independent predictors of severity in P. vivax. Increasing parasite index [2.97 (1.11-7.98)] alone was the independent predictor of severity in P. falciparum. Mortality in vivax and falciparum malaria was 0.34% (95% CI -0.13-0.81%) and 2.21% (95% CI 0.59-3.83%), respectively. Except hyperparasitaemia and shock, other complications were associated (P < 0.05) with mortality in falciparum malaria. Pulmonary oedema/acute respiratory distress syndrome was associated (P = 0.003) with mortality in vivax malaria. Retrospective design of this study possesses inherent limitations. CONCLUSIONS: Plasmodium vivax does cause severe malaria and mortality in substantial proportion but results in much lesser amalgamations of multi-organ involvements than P. falciparum. Pulmonary oedema/acute respiratory distress syndrome in P. vivax infection could lead to mortality and therefore should be diagnosed and treated promptly. Mounting complications and its broadening spectrum in ‘not so benign’ P. vivax warrants global vigilance for any probable impositions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1475-2875-13-304) contains supplementary material, which is available to authorized users.